Structure of component B (7-mercaptoheptanoylthreonine phosphate) of the methylcoenzyme M methylreductase system of Methanobacterium thermoautotrophicum. - Noll, K M (1986)
Component B, the heat-stable low-molecular-weight cofactor required for methane production by dialyzed cell-free extracts of Methanobacterium thermoautotrophicum, has been purified to homogeneity and its structure assigned. Results of low-resolution fast-atom-bombardment and field-desorption mass spectrometry indicated a molecular weight of 419, and high-resolution fast-atom-bombardment mass spectrometry agreed with the molecular formula C13H26NO8PS2. Evidence from fast-atom-bombardment and field-desorption mass spectrometry and 360-MHz 1H NMR in deuterium oxide argued that the compound was isolated as a mixed disulfide with 2-mercaptoethanol; so the proposed elemental formula of the free acid, free thiol would be C11H22NO7PS (molecular weight, 343). The proposed structure for an active form of the coenzyme is 7-mercaptoheptanoylthreonine phosphate.